The radiation dose tolerance of the brachial plexus: A systematic review and meta-analysis. (September 2019) - Yan, Michael; Kong, Weidong; Kerr, Andrew; Brundage, Michael
Highlights: Current brachial plexus dose constraints are based on limited retrospective data Systematic review identified 37 patient cohorts treated with 2D/3D planned techniques. Meta-analysis generated model estimates a 1.11 RR increase in RIBP per 1 Gy bpDmax. Additional detailed dosimetric studies are required to further refine predictive model. Abstract: Purpose: We performed a systematic review and meta-analysis of studies reporting the incidence of radiation induced brachial plexopathy (RIBP) and the associated radiotherapy doses to this structure. Methods: Databases were queried without language restriction for cohort studies reporting RIBP incidence and associated brachial plexus dose maximum dose (bpDmax). Studies specifying RIBP relative risk (RR) effect size were selected for meta-analysis. RRs for RIBP from each study were converted to a regression coefficient (β) and standard error corresponding to a continuous representation of bpDmax. The adjusted β from individual studies were combined using a random effects model and weighted by inverse variance (1/SE 2 ). The trim and fill approach was used to assess publication bias. Results: We identified 25 studies that included 37 unique patient cohorts eligible for analysis. Seventeen cohorts experienced an RIBP incidence ≤5%, of which 6 cohorts exceeded conventional plexus constraints of 60 Gy for bpDmax. Five of the 6 cohorts were simulated with 3D-CT techniques. Meta-analysis of eligible studies demonstrated a significant increase in RIBP risk for each Gy increase in bpDmax (RR, 1.11; 95% CI 1.07–1.15). Results remained significant after adjustment for publication bias and when sensitivity analysis was performed. Conclusions: Our results suggest that current brachial plexus constraints of 60–66 Gy are safe. Meta-analysis provides a log-linear model to quantify the association of brachial plexus dose and RIBP risk, and thus inform the therapeutic ratio for dose escalation. Further prospective studies reporting dosimetric data can better refine this model and inform brachial plexus constraint guidelines.